Rising visceral leishmaniasis in Holy Himalayas (Uttarakhand, India) – A cross-sectional hospital-based study - Sweety Kumari; Piyush Dhawan; Prasan Kumar Panda; Mukesh Bairwa; Venkatesh S Pai (Journal of Family Medicine and Primary Care, 2020)
Background: Apart from the rarity of the visceral leishmaniasis (VL) cases in high altitude (>2000 ft), the combination triad of VL, hemophagocytic lymphohistiocytosis (HLH) syndrome, and Himalayas is rarely being reported. Here, we studied the triad in the Himalayan region, attending a single tertiary care hospital over a period of 2 years. Methods: The study was a cross-sectional analysis of case records of seven confirmed VL patients. A systematic master chart review analyzed the demographic, clinical, laboratory, treatment, and outcome details of these patients. Results: These cases were diagnosed as VL by clinical findings and confirmed by rk-39 anti-body and demonstration of LD bodies in bone marrow smears. All cases without any travel history to endemic regions presented with prolonged fever (>1 months duration), anorexia, weight loss, and having hepatosplenomegaly and bi-or pan-cytopenia. All cases were having HLH, confirmed based on the HScore system (online calculation), and liver injury having transaminitis. Kidney involvement was seen in 27% cases. All cases improved with liposomal amphotericin-B, but one had cardiac arrest after blood transfusion reaction. Conclusion: Clinician of the non-endemic zone should suspect VL in patients with fever of unknown origin and have a high suspicion in cases of HLH and liver involvement and vice versa. Kidney involvement is seen in one-third of the VL cases. Liposomal amphotericin-B is recommended in this region. The leishmaniasis prevalent in these areas should further be subject to comparison with endemic parts, and a large-scale study is needed to find the reason of the rising vector from the holy Himalayas.